Developing Story Book with Pictures to Increase Javanese Skill Ngoko Alus in Early Childhood - Mallevi Agustin Ningrum; Nurulloh Lailatul Jannah (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2021)
The lack of knowledge on the use of Javanese language that is not in accordance with unggah-ungguh, has an impact on the future of the language itself. Therefore, it is important to teach unggah-ungguh, from childhood by doing habituation. This research develops story book in Javanese Ngoko Alus or everyday language. The purpose of this research is to describe the feasibility of picture story books to improve the Javanese language skills of Ngoko Alus in children aged 5 – 6 years. This study uses a research and development method with the ADDIE research model. This study uses observation and questionnaires conducted online via Google form as data collection techniques. The data analysis technique used in this research is quantitative and qualitative data analysis. The results of the feasibility assessment from media experts got a percentage of 88% and material experts got a percentage of 86%, the percentage value was in the very feasible category. The results of the research data obtained from trials to kindergarten teachers in Mojokerto regency, 20 people get a percentage of 85.2%, the percentage value is in the very feasible category. It can be concluded that the Ngoko Alus Javanese picture story book media is feasible to use in learning Javanese.=